Integrating Grammarly Tools to Enhance Writing Efficiency in Senior High School - Like Raskova (Jadila: Journal of Development and Innovation in Language and Literature Education, 2023)
The background of this research is that the writer wants to examine the use of grammar in improving writing efficacy. The purpose of this study was to find out the application of Grammarly to improve the efficiency of writing skills in senior high schools. Researchers used descriptive qualitative methods by using interviews, observations, and questionnaires. In this study, 30 participants were observed, and at the end of the interview, eight students with high questionnaire results were taken to be interpreted. Participants are high school students studying in the 2022/2023 school year. The results and discussion show that Grammarly helps high school students learn writing. Students are interested and confident in using Grammarly with the various advantages available during the learning process. This tool is also practical to use and easy to access, so it doesn't make it difficult for students. Students showed positive views of using Grammarly and felt that it was more helpful in exploring writing skills using Grammarly with their various advantages.